The Abundance, Diversity, and Metabolic Footprint of Soil Nematodes Is Highest in High Elevation Alpine Grasslands - Kergunteuil, Alan; Campos-Herrera, Raquel; Sánchez-Moreno, Sara; Vittoz, Pascal; Rasmann, Sergio (Frontiers in Ecology and Evolution, 2016)
Nematodes are key components of soil biodiversity and represent valuable bio-indicators of soil food webs. Numerous community indices have been developed in order to track variations in nematode-mediate soil ecosystem processes, but their use is mainly restricted to anthropogenic stresses. In this study, we propose to expand the use of nematodes' derived ecological indices in order to shed light on variations of soil food webs in natural systems distributed along elevation gradients. For this purpose, we aimed at determining how elevation affects the community structure and the trophic diversity by studying the abundance, the composition and the functional diversity of nematode communities. Nematode communities were sampled every 200 m across five transects that span about 2000 m in elevation in the Alps. To understand the underlying ecological parameters driving these patterns we studied both abiotic factors (soil properties) and biotic factors (trophic links, relationships with plant diversity). We found that (1) nematode abundance increases with elevation of lowland forests and alpine meadows; (2) differences in nematodes communities rely on habitat-specific functional diversity (e.g., tolerance to harsh environments, “colonizer/persister” status) while most trophic groups are ubiquitous; and (3) the metabolic footprint of the complete nematode community increases with elevation. We thus conclude that the contribution of soil dwelling nematodes to belowground ecosystem processes, including carbon and energy flow, is stronger at high elevation. The resulting cascading effects on the soil food web structure are discussed from an ecosystem functioning perspective. Overall, this study highlights the importance of nematodes in soil ecosystems and brings insights on their functional role along ecological gradients.